Addressing malnutrition in all its forms in Africa requires a radical paradigm shift - Melse‑Boonstra, Alida; Brouwer, Inge D.; Samuel, Folake; Musonda, Mofu (Routledge, 2025)
In the first chapter of this book, four paths of change are highlighted to describe the context of African agri-food systems and how these may change towards 2050. We conclude that neither of these paths will lead Africa towards SHD for its inhabitants, unless an SHD perspective is adopted. Taking the dietary needs of consumers as the starting point in reshaping food systems to deliver SHD represents a long-term investment in a strong workforce and manageable health care expenses. A continued narrow-minded focus on productivity, calories, yields, and inputs of a few staple and cash crops is unlikely to serve human and planetary well-being and equity in Africa. What is needed is leadership and a common long-term vision that guides re-shaping of food systems to nourish the continent.